ChemInform Abstract: Synthesis and Characterization of the Quaternary Thioaluminogermanates A(AlS2)(GeS2) (A: Na, K). Issue 35 (September 2015) - Al‐Bloushi, Mohammed; Davaasuren, Bambar; Emwas, Abdul‐Hamid; Rothenberger, Alexander
Abstract The title compounds are prepared from stoichiometric mixtures of M2S (M: Na, K) and elemental Al, Ge, and S (fused silica ampules, 850 °C, 4 d).